Study of health status of mosques and prayer rooms covered by Kashan University of Medical Sciences in 2019 - Elaheh Mianehsaz (Fiyz̤, 2020)
Background: Taking care of health principals is essential for prevention of diseases and attracting young people to congregational prayers in mosques and prayer rooms. The purpose of this study was to investigate the health status of mosques and prayer rooms under the ownership of Kashan University of Medical Sciences in 2019. Materials and Methods: This is a descriptive cross-sectional study. The standard checklist of the mosque health regulations of the Ministry of Health and Medical Education was used, which included 48 questions (1 to 3 scores), in three areas of personal health, equipment hygiene and construction, and a total of 100 score. The information was collected through direct visits by the trained person in this area. Data was analyzed using excel software. Results: Data from 17 religious places (one mosque, prayer room of dormitories, administrative departments and hospitals) showed that in terms of construction status, 60.5%, in terms of equipment health, 39.6% and in terms of Individual health, 26.8% of the studied sites had favorable conditions. The mosque's status was better than other sites. Prayer rooms of Aran-Bidgol Healthcare, Al-Zahra Dormitory and the Kargarnejad Hospital had the best situation respectively and the Deputy Chancellor of Treatment, Al-Ghadir Dormitory and Matini Hospital's prayer rooms had lowest scores respectively. Conclusion: The status of the prayer rooms in hospitals were worse than the administrative and dormitories. The health statuses of the boy's dormitories were worse than that of girls.